Evaluation of Neuraminidase Inhibitory Activity of Compounds and Extracts from Traditional Medicines by HPLC-FLD - Guangying Yu; Dan Fang (International Journal of Analytical Chemistry)
A simple and effective method was established and validated to determine 4-methylumbelliferone (4-MU) for screening the natural neuraminidase inhibitors (NAIs) from traditional medicines (TMs) by high performance liquid chromatography combined with fluorescence detection (HPLC-FLD). 4-MU and TMs compounds were separated on a Hedera TM ODS column (5 μm, 4.6 × 250 mm) using an isocratic elution of 55% methanol at 35°C. The flow rate was 1 mL min−1. The excitation and emission wavelength were performed at 320 nm and 480 nm. Some extracts of TMs and compounds were selected as examples to demonstrate the feasibility of the new HPLC-FLD method. It was found that the results of most compounds except for the auto fluorescence substances determined by HPLC-FLD were in good agreement with NA enzyme-based inhibitory assays. Comparing to traditional NA enzyme-based inhibitory assays, the HPLC-FLD method could prevent interference from fluorescence pigments of compounds. It was considered a simple, effective, and economical technique for the screening the natural neuraminidase inhibitors from traditional medicines.